Question 1
The given system of equations is:
[tex]y = {x}^{2} + 5x + 6 \\ y = 3x + 6[/tex]
Equate the two equations:
[tex] {x}^{2} + 5x + 6 = 3x + 6[/tex]
Rewrite in standard form:
[tex] {x}^{2} + 5x - 3x + 6 - 6 = 0[/tex]
[tex] {x}^{2} + 2x = 0[/tex]
[tex]x(x + 2) = 0[/tex]
[tex]x = 0 \: or \: x = - 2[/tex]
When we put x=0, in y=3x +6, we get:
[tex]y = 3(0) + 6 = 6[/tex]
One solution is (0,6)
When we put x=-2, into y=3x+6, we get:
[tex]y = 3( - 2) + 6 = 0[/tex]
Another solution is (-2,0)
The solutions are; (0,6) and (-2,0)
Question 2:
The function is
[tex]f(x) = {x}^{6} - {x}^{4} [/tex]
Let us put x=-x,
[tex]f( - x) = {( - x)}^{6} - {( - x)}^{4} [/tex]
This gives:
[tex]f( - x) = {x}^{6} - {x}^{4} [/tex]
We can observe that:
[tex]f(x) = f( - x)[/tex]
This is the property of an even function.
Question 3:
The given function is
[tex]f(x) = {x}^{2} + 3x - 2[/tex]
The average rate of change of f(x) from x=a to x=b is given as:
[tex] \frac{f(b) - f(a)}{b - a} [/tex]
This is the slope of the secant line connecting the two points on f(x)
From x=2 to x=6, the average rate of change
[tex] = \frac{f(6) - f(2)}{6 - 2} \\ = \frac{ {6}^{2} + 3 \times 6 - 2 - {2}^{2} - 3 \times 2 + 2 }{4} \\ = \frac{36 + 18 - 4 - 6}{4} \\ = \frac{44}{4} \\ = 11[/tex]
The average rate of change is 11